Maintaining hope: the intrinsic role of professional support. Issue 1 (9th January 2017) - Onnis, Leigh-ann L.; Dyer, Geraldine
Abstract : Purpose: The purpose of this paper is to examine the supportive aspects of a team approach for a remote mental health team that report high stability in senior clinical roles, in a region where voluntary turnover is typically high. Design/methodology/approach: This qualitative research study examines the reflections of team members on their role and job characteristics through informal semi-structured interviews. Findings: The extant themes identified as supportive aspects of the team approach included engagement and both personal and professional support. The intrinsic role of support in remote work environments, and the impact of intrinsic job satisfaction through client-focussed practices further supported low turnover, improved stability and consistency of service provision. Originality/value: Continued support for existing experienced health professionals will contribute to workforce stability in remote regions where needs are complex and continuity of care is improved by consistent, reliable services. With health professionals working in remote Australia reporting high levels of job satisfaction; it follows that the next steps involve minimising dissatisfaction through effective workforce support mechanisms. Health professionals already working in remote regions, suggest that this is about engagement and personal and professional support through flexible work systems. While the findings of this study may not be generalisable, the authors suggest that these supportive aspects are transferable to other multi-disciplinary team settings.